Integration of Character Education Values from Imam Al-Ghazali's Perspective in Arabic Language Learning at Madrasah Aliyah Negeri 1 Samarinda - Edy Rizki Molyono; Edy Murdani Z (Al-Jawhar : Journal of Arabic Language, 2024)
The learning process in Arabic language subjects, especially in its implementation, has many children who have quite good morals amid rampant cases of intolerance and cases of juvenile delinquency due to the moral degradation of the nation's children. This study aims to determine whether Arabic Language Learning contains character values relevant to Imam Al-Ghazali's perspective in his book Ayuhal Walad and to find out the impact on Madrasah Aliyah Negeri 1 Samarinda students. This type of research is descriptive qualitative using a case study approach. The data collection techniques used are observation, interview, and documentation techniques. Data analysis techniques using Miles and Huberman interactive analysis. The results showed that the values of the Character Education Perspective of Imam Al-Ghazali Relevant to Arabic Language Learning at Madrasah Aliyah Negeri 1 Samarinda. This can be seen in the learning process, such as planning. There are character values of Religion and Hard work, and in the implementation of learning as well, namely Religious, Honest, Hard Work, and Tolerance characters and in the Evaluation also has character values, namely responsibility. Applying these character values also has a good impact on the character and attitude of students after learning.